A study of complex distillation arrangements for improved depropanizing, debutanizing and deisobutanizing fractionation of NGL - Jung, Y.; Long, N.; Woldetensay, Mesfin; Lee, M. (Elsevier, 2012)
The depropanizing, debutanizing and deisobutanizing fractionation steps of processing natural gas liquids were improved through studying complex distillation arrangements, including the double dividing wall column arrangement (DDWC), the sequence including a dividing wall column (DWC) and a bottom DWC (BDWC) and the sequence including a DWC and a BDWC with top vapor recompression heat pump. These arrangements offer benefits by decreasing reboiler and condenser power consumption. Reducing the number of columns and their diameters can potentially reduce construction costs. The result also showed that operating cost could be reduced most significantly through novel combinations of internal and external heat integration: bottom dividing wall columns employing a top vapor recompression heat pump.